2005
DOI: 10.1080/03610730500206808
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Younger and Older Adults' Self-Assessment Manikin Ratings of Affective Pictures

Abstract: Self-Assessment Manikin (SAM) ratings were used to examine whether groups of 21 younger (M age = 20.02 years, SD = 2.28) and 21 older (M age = 66.26 years, SD = 5.64) adults had similar affective experiences to pictures from the International Affective Picture System (Lang, Bradley, & Cuthbert, 1997). The psychometrics of the SAM valence and arousal scales were also compared across age groups. Internal consistency reliability (Cronbach's alpha) was similar for younger and older adults, where both groups made l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
102
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(115 citation statements)
references
References 15 publications
8
102
1
1
Order By: Relevance
“…That is, stimuli that are more extreme in positive or negative valence are also rated as being more arousing (Backs, da Silva, & Han, 2005;Ito, Cacioppo, & Lang, 1998;Lang, Bradley, & Cuthbert, 1998;Libkuman, Otani, Kern, Viger, & Novak, 2007; but for exceptions, see Grühn &Scheibe, 2008, andRibeiro, Pompéia, &Bueno, 2005). In the present study, we asked participants to evaluate the extent to which the symbol refers to something arousing/exciting or passive/calm (1 = Refers to something very passive/calm, 7 = Refers to something very arousing/exciting).…”
Section: Dimensions Of Interestmentioning
confidence: 93%
“…That is, stimuli that are more extreme in positive or negative valence are also rated as being more arousing (Backs, da Silva, & Han, 2005;Ito, Cacioppo, & Lang, 1998;Lang, Bradley, & Cuthbert, 1998;Libkuman, Otani, Kern, Viger, & Novak, 2007; but for exceptions, see Grühn &Scheibe, 2008, andRibeiro, Pompéia, &Bueno, 2005). In the present study, we asked participants to evaluate the extent to which the symbol refers to something arousing/exciting or passive/calm (1 = Refers to something very passive/calm, 7 = Refers to something very arousing/exciting).…”
Section: Dimensions Of Interestmentioning
confidence: 93%
“…Another methodological issue is habituation that may affect subjective ratings. Repeated exposure to the same pictorial stimuli prior to assessment may attenuate the subjectively experienced emotionality and may level out potential age-related differences in subjective ratings (Backs, da Silva, Han, 2005;Denburg, Buchanan, Tranel, & Adolphs, 2003). Age-related differences in rating may also be due to habituation to stimuli over time.…”
Section: Results and Conclusionmentioning
confidence: 99%
“…Reports on physiological measures and subjective ratings of emotional stimuli are mixed (Smith, Hillman, & Duley, 2005). Studies have reported lesser (Mather et al, 2004), greater (Smith el al., 2005), as well as equal (Backs, da Silva, & Han, 2005;Denburg, Buchanan, Tranel, & Adolphs, 2003) emotional responses in older compared to younger adults. In general, aging is associated with attenuated physiological activity.…”
Section: Aim and Backgroundmentioning
confidence: 92%
See 1 more Smart Citation
“…This study applied a pencil-and-paper version of the Self-Assessment-Manikin (SAM) [16], a non-verbal self-report instrument whose main attribute is its reduction of the cognitive processing bias when measuring Type 1 affective responses. Numerous studies have proven the validity and reliability of the SAM method [18,19,20]. SAM is a 9-point picture-scale that directly measures the two major affective dimensions 4 : pleasure and arousal [14].…”
Section: Measuring Affectmentioning
confidence: 99%